LEARNING MEDIA SIMULATION OF SIGNAL PROCESSING USING JAVASCRIPT PROGRAMMING LANGUAGE AS ALTERNATIVE TO DISTANCE LEARNING. - PURNAMA, A. Y.; ARISWAN, A.; ISTIYONO, E.; KUSWANTO, H.; PUTRANTA, H.; SETYAWAN, D. N.; SAPUTRI, R. (Revista Cubana de Física)
The main objective of this research is to create a signal processing simulation using Javascript programming language on acoustic waves. Signal processing uses Fourier Transform to convert signals from the time domain to the frequency domain. Acoustic wave samples were obtained from a Javanese musical instrument called Gamelan. Acoustic wave signals from Gamelan are chosen because there is still little research on Gamelan signal processing. This research has successfully created a simulation using Javascript programming language. The simulation can show the waveform in function of time and its wave spectrum. The convenience of this tools for distant learning is substantiated.